Data visualization as creative art practice. (August 2018) - Li, Qi
This article begins by tracing the evolution of data visualization from the fields of aesthetics to areas of creative practice, arguing that the emergence of big data presents creative potential for digital artists. Whereas conventional information visualization emphasizes the effective understanding of data, aesthetics considers the possibility that visualization can enhance the experience of data and support the acquisition of knowledge. In expressing an artistic intent or form, data-based creative practices synthesize and build upon techniques in communications and aesthetics. The article provides a review of recent digital art projects involving big data and suggests further directions for creative practice in an era of data proliferation.